Morphology engineering of cobalt embedded in nitrogen doped porous carbon as bifunctional oxygen electrocatalyst for Zn-air battery. (September 2020) - Li, Y.; Cui, M.; Wang, C.; Chen, Y.; Chen, S.; Gao, L.; Liu, A.; Su, W.-N.; Ma, T.
Abstract: The structure and morphology of catalysts can affect their catalytic performance due to the various exposed active sites and mass transport pathway. Herein, we synthesis a serious of Co-based complex with spindle-like, branched spindle, disk-like and quasi-sphere morphologies and found that the crystal growth is controlled by multistep crystal splitting mechanism. We further transferred the Co-based complex into Co embedded in nitrogen doped porous carbon (Co@NC) by thermal annealing to investigate the morphology effect of electrocatalysts. It was found the catalytic performance of the catalysts exhibits a trend of quasi-sphere (Co@NC-80) > spindle-like (Co@NC-300) > branched spindle (Co@NC-200) > disk-like (Co@NC-130), probably due to the various exposed efficient active sites of the catalyst induced by their morphology, and various mass transport resistance in the catalysts. Impressively, the Co@NC-80 exhibits comparable ORR (oxygen reduction reaction) activity with Pt/C and better OER (oxygen evolution reaction) activity than RuO2, highlighting its bifunctional catalytic performance for metal-air batteries. The Zn-air catalyzed by Co@NC-80 exhibits an open circuit voltage of 1.35 V, a high specific capacity of 887.5 mA h/g and a max power density of 168.7 mW cm −2, as well as excellent long-time stability with no obvious performance decay after charge-discharge cycling of 140 h. Graphical abstract: A serious of Co embedded in nitrogen doped porous carbon (Co@NC) was synthesized and the morphology effect toward electrocatalysis is investigated. Image 1 Highlights: A serious of Co-based complex with various morphologies was synthesized via crystal splitting mechanism. The Co@NC-x was synthesized to investigate their morphology effect for electrocatalysis. The Co@NC-x shows various exposed efficient active sites and mass transport resistance. The Co@NC-80 shows good bifunctional activity for ORR and OER. The Zn-air catalyzed by Co@NC-80 exhibits better performance than that for Pt/C+RuO2 .